BAHASA HEWAN DAN MANUSIA - Aditya Widiawan; Yeni Ega Susanti; Silvina Noviyanti (STKIP Subang, 2024)
Language is a tool of human communication, through language humans can understand the meaning of our thoughts and words when communicating socially. Based on their research on several animal species, it is known that many animals have complex and intelligent ways to signal danger and communicate their basic needs. The method used in writing this article is a literature review or literature study, which is an article prepared based on a literature search, both national and international. The nature of language is unique and universal. A language that is unique means that each language has its own characteristics that other languages ​​do not necessarily have. Animal and human languages ​​have differences in that animal language is an instinctual language that does not need to be learned, while human language is a science that needs to be developed.